Pengaruh Pengalaman Pembelajaran Praktik dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Siswa pada Instalasi Penerangan Listrik - Purnarbawa, Regan Pandya; Achmad, Fendi; Zuhrie, Muhamad Syariffuddien; Fathoni, Ali Nur (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Vocational electrical education demands strong practical competence, yet many students merely imitate peers' work instead of reasoning through problems independently, leaving critical thinking underdeveloped. This study examined the effect of practical learning experience and critical thinking ability on students' knowledge and skill learning outcomes in the Electrical Lighting Installation subject taught through Project Based Learning. A quantitative ex-post facto design was applied to 74 twelfth-grade Electrical Power Installation students selected through purposive sampling. Partial tests (t-test) showed that practical learning experience significantly affected knowledge outcomes (t = 2.625; Sig = 0.011; contribution 18.6%) and skill outcomes (t = 3.185; Sig = 0.002; contribution 16.5%). Critical thinking ability significantly affected knowledge outcomes (t = 3.138; Sig = 0.002; contribution 17.9%) and skill outcomes (t = 2.716; Sig = 0.008; contribution 13.4%). Simultaneously, both variables significantly predicted knowledge outcomes (F = 4.979; Sig = 0.009) and skill outcomes (F = 5.100; Sig = 0.009). These findings confirm that strengthening practical experience and critical thinking together contributes to improved learning outcomes in project-based vocational electrical education.